Implementation of Line Card Number Media in Improving Elementary School Students’ Addition and Subtraction Ability - Inayah, Ismatun; Mustoip, Sofyan; Somantri, Somantri (EduBase : Journal of Basic Education, 2024)
This research aims to explore the implementation of Line Card Number media in improving the addition and subtraction abilities of elementary school students at MIS Dar Al Tauhid, Cirebon City. This research uses a qualitative method with a case study approach. Data was collected through direct observation, in-depth interviews with teachers and students, as well as analysis of documents related to the learning process using Line Card Number media. The research results show that the use of Line Card Number media helps students understand the concepts of addition and subtraction more easily and interactively. Teachers reported an increase in student participation during learning, as well as a decrease in errors in solving addition and subtraction problems. Students also stated that this media made them more interested and motivated in learning mathematics. The conclusion of this research is that the Line Card Number media is effective as a learning tool to increase students' understanding of addition and subtraction operations. This media not only makes the learning process more interesting but also helps students internalize basic mathematical concepts in a deeper and more enjoyable way.